2015
DOI: 10.1111/jcpe.12345
|View full text |Cite
|
Sign up to set email alerts
|

Adjunctive moxifloxacin in the treatment of generalized aggressive periodontitis patients: clinical and microbiological results of a randomized, triple‐blind and placebo‐controlled clinical trial

Abstract: The results from this study suggest that moxifloxacin as and adjunct to one-stage full-mouth SRP leads to a better clinical and microbiological advantages compared to mechanical treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(49 citation statements)
references
References 43 publications
2
44
0
3
Order By: Relevance
“…Systemic levofloxacin and moxifloxacin improve the clinical outcomes of periodontitis and suppress A actinomycetemcomitans below detectable levels. 14,15 In our case, the antibiotic resistance to levofloxacin before the corneal transplantation, however, was contrary to these reports, but was consistent with histopathologic results; this revealed that the infection focus was located in the deep corneal stroma, leading to poor corneal drug penetration and a low antibiotics concentration. Similarly to an Actinomyces-induced keratitis case after keratoplasty, 6 A actinomycetemcomitans was difficult to eradicate medically in our case, and required surgical intervention.…”
Section: Discussionsupporting
confidence: 74%
“…Systemic levofloxacin and moxifloxacin improve the clinical outcomes of periodontitis and suppress A actinomycetemcomitans below detectable levels. 14,15 In our case, the antibiotic resistance to levofloxacin before the corneal transplantation, however, was contrary to these reports, but was consistent with histopathologic results; this revealed that the infection focus was located in the deep corneal stroma, leading to poor corneal drug penetration and a low antibiotics concentration. Similarly to an Actinomyces-induced keratitis case after keratoplasty, 6 A actinomycetemcomitans was difficult to eradicate medically in our case, and required surgical intervention.…”
Section: Discussionsupporting
confidence: 74%
“…Adjunctive MOX reduced subgingival A. actinomycetemcomitans to undetectable levels after 6 months, and a significant reduction in the levels of P. gingivalis in GAgP patients and chronic periodontitis individuals has been observed . Furthermore, Ardila et al .…”
Section: Introductionmentioning
confidence: 94%
“…Combinations of amoxicillin and metronidazole (AMOX + METRO) or doxycycline with mechanical treatment have essentially resolved periodontal inflammation found in patients with generalized AgP (GAgP) . Our research group also recently showed that moxifloxacin (MOX), as an adjunct to one‐stage, full‐mouth SRP, leads to a better clinical and microbiological advantages compared to mechanical treatment . The synergistic effect of AMOX + METRO is of particular importance in GAgP patients who yielded a high prevalence of A. actinomycetemcomitans and anaerobic pathogens in the subgingival microbiota; however, adjunctive antimicrobial treatment has been applied empirically …”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…(13,16) Estos resultados se pueden explicar debido a que la composición de la microflora subgingival difiere notablemente entre pacientes y grupos étnicos y geográficos. (7,8) La comprensión de la forma como se organiza y cambia la flora microbiana subgingival en la PAgG promueve la elección de terapias antibióticas adjuntas a la terapia mecánica; antimicrobianos como la azitromicina o la doxiciclina sin efectos importantes sobre la flora subgingival no se deben contemplar para el tratamiento en pacientes con este tipo de periodontitis, (18,19) por el contrario terapias como amoxicilina y metronidazol, (20) o la más recientemente propuesta moxifloxacina, (21) muestran una eficacia importante en el manejo coadyuvante farmacológico de la PAgG. Diferentes reportes muestran la presencia de bacilos entéricos gram-negativos en bolsas de pacientes diagnosticados con periodontitis, (22,23) en nuestro estudio 10% de los pacientes presentaron resultado positivo para estos microorganismos, lo que confirma la participación de bacilos entéricos en la conformación del ecosistema de la periodontitis, sin embargo no se ha esclarecido el papel de ellos en la patogenia de la enfermedad.…”
Section: Sas ( Mm±sd ) 32%unclassified